EVALUASI IMPLEMENTASI KEBIJAKAN PENATAAN DAN PEMERATAAN GURU PEGAWAI NEGERI SIPIL (PNS) SMA NEGERI DI DKI JAKARTA - Eni Rindarti (Jurnal Pendidikan Islam, 2018)
The objective of this research is to explain about policy implementation of structuring and equity of the Civil Servants teacher at State High School in DKI Jakarta. In this evaluation research Stake's Countenance Model is used. It consists of three components namely antecedents, transactions, and outcomes. The data were collected through document analysis, interview, and observations. Sources of data in this study consists of the educational administrators, school supervisors, school principals, and teachers. The results show that: policy implementation structuring and equalization of civil service teachers at high schools in Jakarta has not run optimally. There are aspects of the three components of the policy (antecedent, transactions, and outcomes) that should be improved, namely: program planning and socialization activities, mechanisms of activity implementation, as well as monitoring including guidance and supervision so as to provide a positive impact towards fulfilling the needs and redistribution of teachers, and improving the performance and competence of teachers.